EFL Teacher's Stance and Engagement in Digital Multimodal Composing as Multimodal Literacy Practices - Novia - Trisanti; Didi - Sukyadi; Budi - Hermawan (International Journal of Education, 2024)
The ability of EFL teachers to design and carry out multimodal literacy practices that accurately reflect the performance of EFL learners is on challenging demands. However, the research on multimodal literacy practices, including digital multimodal composing (DMC) is still in early stages although it is increasingly being used in EFL classroom. This study used DMC combined with active learning techniques to attain the learning goals. Its purposes are to look at how EFL teachers in higher education develop the procedures for using DMC for the student's project and to scrutinize their engagement in influencing the learner's writing creativity. The case study was applied in an EFL environment in Indonesian context using field notes, and an interview as the teacher’s reflection. The results demonstrate that the EFL teacher was involved in remediation stance for the DMC tasks designed to encompass students produce multimodal texts using Canva, for example, reading response and biography recount text mind mapping. It reveals that the teacher used the DMC task alongside another media as an assessment tool. While using DMC as the learners' projects for the assessment, the teacher's engagement was ambivalent, meaning that the teacher was fond of using DMC as the learning evaluation. More research is therefore required to better understand how DMC helps teachers develop their knowledge regarding the practice of multimodal literacy in the EFL context. Keywords: Digital Multimodal Composing, EFL Context, Teacher’s Stance and Engagement